1996
DOI: 10.1192/bjp.168.3.308
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenology and Course of Generalised Anxiety Disorder

Abstract: This prospective study confirms the chronicity associated with GAD and extends this finding to define the one and two year remission rates for the disorder. Likelihood of remission for GAD and any other comorbid condition after one year was half the annual remission rate for GAD alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
125
5
5

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 223 publications
(145 citation statements)
references
References 20 publications
(2 reference statements)
10
125
5
5
Order By: Relevance
“…Follow-up studies are short and chronicity is marked, even in the face of treatment. In a 2-year follow-up of a specialist clinical sample, 88% stayed at the same symptom level over the first 6 months and only 25% experienced a period of remission exceeding 8 weeks during the follow-up period despite virtually all patients being actively treated (17). In a 5-year follow-up only 18% of another specialist clinical sample had no symptoms and 46% still met full criteria (18).…”
Section: Background Informationmentioning
confidence: 97%
“…Follow-up studies are short and chronicity is marked, even in the face of treatment. In a 2-year follow-up of a specialist clinical sample, 88% stayed at the same symptom level over the first 6 months and only 25% experienced a period of remission exceeding 8 weeks during the follow-up period despite virtually all patients being actively treated (17). In a 5-year follow-up only 18% of another specialist clinical sample had no symptoms and 46% still met full criteria (18).…”
Section: Background Informationmentioning
confidence: 97%
“…Recent research has shown that suffering from GAD is related to increased suicidal ideations or attempts, even after symptoms of comorbid Axis I disorders and stressful life events are statistically controlled (Boden et al 2007). The typical age of onset for GAD occurs in adolescence and early adulthood (Kessler et al 2007;Yonkers et al 1996). The clinical course of the disorder is considered to be chronic because most patients are still affected 6-12 years after the initial diagnosis (Yonkers et al 2000).…”
Section: Generalized Anxiety Disordermentioning
confidence: 99%
“…Generalized anxiety disorder seems to be one of the most frequent diagnoses 5,6 and its chronic course 7 and negative impact on quality of life is recognized 8 . Some studies using epidemiologic samples indicate that this specific disorder and alcohol or drug use co-occur and are associated 9,10 .…”
Section: Introductionmentioning
confidence: 99%